2017
DOI: 10.2147/cia.s149493
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and preoperative health-related quality of life on patient-reported improvements after total hip arthroplasty

Abstract: BackgroundTotal hip arthroplasty (THA) is a common surgical procedure and approximately 9,500 of these surgeries are performed annually in Denmark. The operation is considered effective and successful with respect to complications, mortality, and implant survival. However, using patient-reported outcome measures, up to 10% of patients are not satisfied with the outcome of their operation. To address this, it is important to find out why some patients experience impaired outcomes after THA. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…In the follow up after 12 months, both groups had a median EQ-5D of 1.0 for the ERAS and non-ERAS groups. The studies of Larsen et al [ 19 ] and Aalund et al [ 20 ] showed comparable results to our study, with a continued rise of the values of EQ-5D to the follow up after 12 months. Preoperatively, both groups showed an inferior score compared to the population norm of Germany.…”
Section: Discussionsupporting
confidence: 91%
“…In the follow up after 12 months, both groups had a median EQ-5D of 1.0 for the ERAS and non-ERAS groups. The studies of Larsen et al [ 19 ] and Aalund et al [ 20 ] showed comparable results to our study, with a continued rise of the values of EQ-5D to the follow up after 12 months. Preoperatively, both groups showed an inferior score compared to the population norm of Germany.…”
Section: Discussionsupporting
confidence: 91%
“…However, a subgroup analysis of the nondisplaced FNF patients with IF conducted to elaborate the results of the different osteosynthetic treatments (e.g., cancellous screws versus DHS) was not performed in the FAITH trial [37] or in our study. The two large RCTs currently being conducted in Sweden (HipSTHeR trial [38]) and in Denmark (SENSE trial [39]) comparing IF including screw fixation or DHS with THR or Furthermore, overall satisfactory long-term HRQoL has been described in the literature, especially for older patients treated for nondisplaced FNFs with IF as well as for those undergoing primary elective THR [14,40]. In line with recent findings [14,28], we observed that the difference in HRQoL between the IF and HA groups remained proportionate throughout the follow-up period and that the EQ-5D index scores did not differ between the groups.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the existing literature which analyzes continuous PROM scores may report results that hinge on a small subset of patients who do very well or very poorly. Patients who may be outliers postoperatively are those who are unusually healthy and active preoperatively [42,43]. Graves et al [5] proposed that a selfselection bias of more active patients toward a surgeon performing the direct anterior approach may exist.…”
Section: Discussionmentioning
confidence: 99%